(untitled) (Research, Society and Development, 2020)
This article aims to understand how nurses see their assistance in the face of the terminality of life, with regard to the issue of humanization in the daily life of their work process. Based on an integrative literature review carried out in December 2019, based on Scientific Electronic Library Online (SciELO), Latin American and Caribbean Literature in Health Sciences (LILACS), Medical Literature Analysis and Retrieval Sistem on-line (Medline ), and Database in Nursing (BDENF), including articles available in full, published between the years 2014 to 2019, were found 2,736 articles and of these, 08 articles were selected that allude to the theme of the study and fit the inclusion criteria. After thorough reading and careful analysis of the articles, 2 categories emerged: Terminality of life, humanization and special care from the different perspective of the nurse, and Care provided, communication and experiences acquired in the care of terminally ill patients. Despite the number of occurrences of articles in the various databases dealing with the themes of Humanization, Terminality of Life and Palliative Care, a tenuous approach was identified in the nurses’ work practice as a highlight within the care process for terminally ill patients, but it remained It is evident that there are still many challenges to be overcome in the practice of necessary special care, which reinforce the role of the nurse as a differentiated professional, who is able to act and promote dignified care, enabling well-being in the process of finiteness of a patient’s life.